COmparative studies of lipase form germinating and non-germinating coconut (cocos nuciefera linn) kernel powder - Mohd Amin Mohd Hatta (2013)
The purpose of these studies is to determine the lipase activity and characterization of the lipase under different condition fromgerminating and non-germinating coconut (Cocos nucifera Linn) kernel powder which collected from the market area near Jeli, Kelantan. Lipase (triacylglycerol acylhydrolases, EC 3.1.1.3) hydrolyize the triacyiglycerols to diacylglycerols, monoacylglycerols, fatty acid and glycerol The versatility of lipases in catalyzing different kinds of reactions associated with their different specificities endows these enzymes with an important and vast application potential. The extraction of crude enzyme from the kernel powder by using NaC1 0.09% as buffer. The protein concentration determined by using Lowry et al. (1951) method that using Bovine Serum Albumin (BSA) as a standard. Gel filtration chromatography test used to filtrate the sample to several fraction, these fraction contain different protein concentration. Then the temperature and pH optima analysis test was used to find the maximal activity of lipase on different condition, and germinating coconut show maximal activity at 37°C and pH 8, while non-germinating coconut show maximal activity at 40 °C and also pH8. The test proceed by conducting SDS-PAGE gel electrophoresis. From the result the molecular weight of lipase from germinating and , non-germinating coconut was between 48 kDa (fumerase) and 68 kDa (BSA).